Combined therapy with methotrexate nanoconjugate and dendritic cells with downregulated IL-10R expression modulates the tumor microenvironment and enhances the systemic anti-tumor immune response in MC38 murine colon carcinoma - Szczygieł, Agnieszka; Węgierek-Ciura, Katarzyna; Wróblewska, Anna; Mierzejewska, Jagoda; Rossowska, Joanna; Szermer-Olearnik, Bożena; Świtalska, Marta; Anger-Góra, Natalia; Goszczyński, Tomasz M.; Pajtasz-Piasecka, Elżbieta (Frontiers in Immunology, 2023)
Background: Understanding the negative impact of the tumor microenvironment on the creation of an effective immune response has contributed to the development of new therapeutic anti-cancer strategies. One such solution is combined therapy consisting of chemotherapeutic administration followed by dendritic cell (DC)-based vaccines. The use of cytostatic leads to the elimination of cancer cells, but can also modulate the tumor milieu. Moreover, great efforts are being made to increase the therapeutic outcome of immunotherapy, e.g. by enhancing the ability of DCs to generate an efficient immune response, even in the presence of immunosuppressive cytokines such as IL-10. The study aimed to determine the effectiveness of combined therapy with chemotherapeutic with immunomodulatory potential – HES-MTX nanoconjugate (composed of methotrexate (MTX) and hydroxyethyl starch (HES)) and DCs with downregulated expression of IL-10 receptor stimulated with tumor antigens (DC/shIL-10R/TAg) applied in MC38 murine colon carcinoma model. Methods: With the use of lentiviral vectors the DCs with decreased expression of IL-10R were obtained and characterized. During in vivo studies MC38-tumor bearing mice received MTX or HES-MTX nanoconjugate as a sole treatment or combined with DC-based immunotherapy containing unmodified DCs or DCs transduced with shRNA against IL-10R (or control shRNA sequence). Tumor volume was monitored during the experiment. One week after the last injection of DC-based vaccines, tumor nodules and spleens were dissected for ex vivo analysis. The changes in the local and systemic anti-tumor immune response were estimated with the use of flow cytometry and ELISA methods. Results and Conclusions: In vitro studies showed that the downregulation of IL-10R expression in DCs enhances their ability to activate the specific anti-tumor immune response. The use of HES-MTX nanoconjugate and DC/shIL-10R/TAg in the therapy of MC38-tumor bearing mice resulted in the greatest tumor growth inhibition. At the local anti-tumor immune response level a decrease in the infiltration of cells with suppressor activity and an increase in the influx of effector cells into MC38 tumor tissue was observed. These changes were crucial to enhance the effective specific immune response at the systemic level, which was revealed in the greatest cytotoxic activity of spleen cells against MC38 cells.